3x−x2 | ||
∫√6x−x2dx=x√6x−x2−∫ | dx | |
√6x−x2 |
6x−x2−3x | ||
∫√6x−x2dx=x√6x−x2−∫ | dx | |
√6x−x2 |
3x | ||
∫√6x−x2dx=x√6x−x2−∫√6x−x2dx+∫ | dx | |
√6x−x2 |
3−x−3 | ||
2∫√6x−x2dx=x√6x−x2−3∫ | dx | |
√6x−x2 |
1 | ||
2∫√6x−x2dx=x√6x−x2−3√6x−x2+9∫ | dx | |
√6x−x2 |
dx | ||
2∫√6x−x2dx=(x−3)√6x−x2+9∫ | ||
√9−(x−3)2 |
9 | dx | ||||||||||||
2∫√6x−x2dx=(x−3)√6x−x2+ | ∫ | ||||||||||||
3 |
|
x−3 | ||
2∫√6x−x2dx=(x−3)√6x−x2+9arcsin( | ) | |
3 |
1 | 9 | x−3 | ||||
∫√6x−x2dx= | (x−3)√6x−x2+ | arcsin( | )+C | |||
2 | 2 | 3 |